MODEL LOGISTIK DENGAN DIFUSI PADA PERTUMBUHAN SEL TUMOR EHRLICH ASCITIES - Nirwansah, Hendi; Widowati, Widowati (MATEMATIKA, 2007)
This paper presents an approach of the Ehrlich ascities tumor growth modelling based on the logistic equation with diffusion. This model is constructed by using the concept of the reaction-diffusion equation. Besides that by using the principle of the travelling wave, a model equation with diffusion at tumor cell growth can be formed into the two non linear differential equation system. Then the equilibrium points of the non linear system will be obtained so that the stability of the model can be analized.